Riesgos y retos para los profesionales de las disciplinas estomatológicas ante la COVID-19 - Denia Morales Navarro (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: Dental procedures involve frequent exposure to saliva, blood and other fluids, so there is a risk of nosocomial infection with COVID-19. Objective: To describe the transmission of COVID-19, measurements and current situation in dentistry. Material and methods: A bibliographic review was carried out in April, 2020. Journals from the Web of Sciences were fundamentally evaluated. All publications included were from 2020, in English and Spanish. Descriptors such as: "coronavirus infections" and "transmission" were used. Development: The angiotensin-II converting enzyme has a level of expression in oral tissues that is higher in the tongue. Saliva is a means of transmission. Many health workers have been infected and died during the pandemic. Dental patients and professionals can be exposed to viruses that infect the oral cavity and the respiratory tract; therefore, recommended measures include cessation of elective activities, use of barrier elements, and aerosol control. Conclusions: Saliva is the main means of transmission by COVID-19 in dentistry and the aerosols originated in the care increase the risk of contamination. Recommended measures include using means of protection and carrying out surface disinfection. Many countries suspended dental care, except for urgent care.